The Use of Collaborative Strategic Reading to Teach Reading - Sara Rifqi (Research in English and Education Journal, 2018)
The objective of this research is to investigate the types of grammatical errors made by the sixth semester English department students of Syiah Kuala University in writing.  The method used in this research was quantitative in nature.  The samples of this research were 20 English Department Students of Syiah Kuala University using writing test on the descriptive text. The data were analysed that focus on omission, addition, misformation, and misordering. The result found that the most common type of errors made by the students is misformation (47 errors), followed by omission (43 errors), addition (6 errors), misordering (5 errors). So, it can be concluded that students still made errors in their writing. Hence, this research result can give information for the teachers or readers about the types of grammatical error committed by the students. Thus, through the error analysis, the lecturers should give more detailed grammar teaching materials to the students.